2015
DOI: 10.1007/s40266-015-0243-3
|View full text |Cite|
|
Sign up to set email alerts
|

Can We Identify Patients with High Risk of Osteoarthritis Progression Who Will Respond to Treatment? A Focus on Epidemiology and Phenotype of Osteoarthritis

Abstract: Osteoarthritis is a syndrome affecting a variety of patient profiles. A European Society for Clinical and Economic Aspects of Osteoporosis and Osteoarthritis and the European Union Geriatric Medicine Society working meeting explored the possibility of identifying different patient profiles in osteoarthritis. The risk factors for the development of osteoarthritis include systemic factors (e.g., age, sex, obesity, genetics, race, and bone density) and local biomechanical factors (e.g., obesity, sport, joint inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(79 citation statements)
references
References 78 publications
2
75
0
2
Order By: Relevance
“…[4,5]. Recent investigations have also stressed the interest of OA phenotypes identification to understand the variety of pathophysiological processes responsible for disease progression in order to provide a more personalized clinical approach [6]. Osteoporosis is the most common skeletal disease in humans [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4,5]. Recent investigations have also stressed the interest of OA phenotypes identification to understand the variety of pathophysiological processes responsible for disease progression in order to provide a more personalized clinical approach [6]. Osteoporosis is the most common skeletal disease in humans [7].…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have shown an increased prevalence of OA in postmenopausal women suggesting a relationship between estrogen deprivation and the development of OA [16,17]. In fact, estrogen deficiency-related OA has been proposed as a subset of OA [6].…”
Section: Introductionmentioning
confidence: 99%
“…Although several advances have been made in the last years, even now there is much to be done. For this aim, improvements in imaging technologies and analytical validation of multiplex analyses by targeted proteomics will be highly useful to facilitate the identification and qualification of sensitive and specific imaging or biochemical markers [19]. Furthermore, knowledge being currently acquired on the diverse OA phenotypes must be employed in clinical development plans in order to adopt a personalized medicine mindset, trying to pair patient subpopulations with the right therapeutic modes of action [20].…”
Section: Resultsmentioning
confidence: 99%
“…En este estudio, a pesar de que se utilizaron criterios estrictos para clasificar a los pacientes como portadores de SM 21 , su prevalencia en pacientes con y sin gonartrosis fue del 79.9 y el 59%, respectivamente, siendo más altas que en otros reportes 3,22,23 , posiblemente debido a que esos estudios fueron realizados con mayor población y en variados grupos de edad, y en cambio esta investigación tuvo una proporción alta de participantes de edad avanzada. Se han estudiado numerosos factores que pueden incidir en la aparición de gonartrosis u otros tipos de artrosis, como el sexo, la diabetes mellitus, la hipertensión arterial y el índice de masa corporal, pero hasta hace poco tiempo el SM en su conjunto no había sido investigado exhaustivamente como un posible factor asociado 5,12,24,25 . En este estudio, el SM y algunos de sus componentes mostraron ser más prevalentes en estadios de degeneración articular, similar a lo observado por Yoshimura, et al 24 , aunque ellos encontraron otros factores de progresión a gonartrosis más grave, como el sexo femenino y la edad 24 , distinto a lo encontrado en este trabajo, en el cual el sexo femenino y la edad no mostraron ser factores asociados a gonartrosis, esto último posiblemente por el predominio ya referido de pacientes con edad avanzada de la muestra.…”
Section: Discussionunclassified